A world without ice - Björnsson, Helgi (Arctic Portal, 2011)
Professor. Helgi Björnsson, Institute of Earth Sciences, University of Iceland, talks here in the NRF 6th open assembly in Hveragerði, Iceland, in September of 2011. Please click on the link above to see the video.